Notes on Professor and Historian Benjamin Stora Report "The Memory File" - Saoudi, mourad; ameziane, Hussein (The Algerian Historical Journal, 2026)
Issues of historical memory are among the most complex issues to study, due to their great role in shaping the present and future of peoples, because they are a collective narrative that can be produced and reproduced according to specific perceptions and goals. There is usually political manipulation of the historical memory of peoples to fragment their culture. In this direction, we studied a report by historian Benjamin Stora on issues of memory related to French colonialism in Algeria, in a manner that the historian considers his own way of knowing the motives and path of all memory groups in order to reduce ready-made ideas. This report was at the request of the French presidency due to a need dictated by the political circumstances and the nature of the relationship between Algeria and France, which makes this report a fertile field for colonial superiority ideas that manipulate the memory of Algerians and perpetuate the idea of subordination and guardianship over them.